Purified fibers in chemically defined synthetic diets destabilize the gut microbiome of an omnivorous insect model - Dockman, Rachel Louise; Ottesen, Elizabeth A. (Frontiers in Microbiomes, 2024)
The macronutrient composition of a host’s diet shapes its gut microbial community, with dietary fiber in particular escaping host digestion to serve as a potent carbon source for gut microbiota. Despite widespread recognition of fiber’s importance to microbiome health, nutritional research often fails to differentiate hyper-processed fibers from cell-matrix-derived intrinsic fibers, limiting our understanding of how individual polysaccharides influence the gut community. We use the American cockroach (Periplaneta americana) as a model system to dissect the response of complex gut microbial communities to dietary modifications that are difficult to test in traditional host models. Here, we designed synthetic diets from lab-grade, purified ingredients to identify how the cockroach microbiome responds to six different carbohydrates (chitin, methylcellulose, microcrystalline cellulose, pectin, starch, and xylan) in otherwise balanced diets. We show via 16S rRNA gene profiling that these synthetic diets reduce bacterial diversity and alter the phylogenetic composition of cockroach gut microbiota in a fiber-dependent manner, regardless of the vitamin and protein content of the diet. Comparisons with cockroaches fed whole-food diets reveal that synthetic diets induce blooms in common cockroach-associated taxa and subsequently fragment previously stable microbial correlation networks. Our research leverages an unconventional microbiome model system and customizable lab-grade artificial diets to shed light on how purified polysaccharides, as opposed to nutritionally complex intrinsic fibers, exert substantial influence over a normally stable gut community.